A Review of Diverse Halide Perovskite Morphologies for Efficient Optoelectronic Applications. Issue 2 (18th November 2019) - Zhang, Chengxi; Kuang, Dai‐Bin; Wu, Wu‐Qiang
Abstract: Recent years have witnessed an incredibly high fever in metal halide perovskite materials due to their promising applications in a wide range of optoelectronic applications. The morphologies and optoelectronic properties of the perovskite layers play critical roles in affecting the optoelectronic performances. This review summarizes the recent advances in the fabrication of a variety of perovskite morphologies and their promising progress achieved in different optoelectronic applications, including solar cells, light‐emitting diodes, photodetectors, lasers, photocatalysis, X‐ray detectors/imagers, and luminescent solar concentrators. Several blossoming representatives, including 0D perovskite quantum dots, 1D perovskite nanowires, 2D perovskite nanosheets/nanoplatelets, and 3D textured perovskite assemblies (i.e., cuboid‐like, inverse opal‐like, coral‐like, or maze‐like morphologies, etc.), are highlighted to demonstrate their fascinating properties and outstanding capabilities for efficient optoelectronic applications. Finally, a perspective on the remaining challenges and future directions of fabricating unique perovskite morphologies for next‐generation high‐performance optoelectronic devices is provided. Abstract : This review summarizes the recent advances in the fabrication of halide perovskite films with diverse morphologies as well as fascinating optical and photoelectric properties for a wide range of efficient optoelectronic applications.